Participation of Wild Species Genus Avena L. (Poaceae) of Different Ploidy in the Origin of Cultivated Species According to Data on Intragenomic Polymorphism of the ITS1-5.8S rRNA Region - Alexander A. Gnutikov; Nikolai N. Nosov; Igor G. Loskutov; Alexander V. Rodionov; Victoria S. Shneyer (Plants)
The possible origin of four cultivated species of the genus Avena of different ploidy and different subgenome composition (A. strigosa, A. abyssinica, A. byzantina, and A. sativa) from possible wild species was investigated. The region of the internal transcribed spacer ITS1 and the 5.8S rRNA gene in the cultivated species was studied with next-generation sequencing (NGS), and the patterns of occurrence and distribution of the ribotypes were compared among them and with those of the wild species. According to these data diploid, A. strigosa is more closely related to the diploid A. hirtula than to polyploid oats, and it could have evolved independently of polyploid cultivated species. The tetraploid Avena abyssinica could be a cultivated derivative of A. vaviloviana. Two hexaploid cultivated species, A. byzantina and A. sativa, could have a different origin; A. sativa could be the cultivated form of A. fatua, whereas A. byzantina could originate independently. It was found that the oat species with the A and C subgenomes, even with strong morphological and karyological differences, could intercross and pass the further stages of introgression producing a new stable combination of genomes. Our data show that almost all species of Avena could form an introgressive interspecies complex.